Anti-Inflammatory Effects of Novel Glycyrrhiza Variety Wongam In Vivo and In Vitro - Yun-Mi Kang (MDPI AG, 2021)
Licorice is the common name of Glycyrrhiza species, which is an important plant for edible and medicinal purposes; however, Glycyrrhiza resources have become limited because of desertification, depletion of natural resources, and environmental restrictions. For this reason, a novel Glycyrrhiza variety named Wongam, a hybrid of G. glabra and G. uralensis, was developed by the Korea Rural Development Administration. To elucidate the antiallergic inflammatory effects of Wongam, we investigated its effects using a compound-48/80-induced anaphylaxis in vivo model and PMA/A23187-stimulated HMC-1 cells and immunoglobulin E (IgE)/DNP-stimulated RBL-2H3 cells in in vitro models. Wongam treatment reduced mortality and serum IgE levels and downregulated proinflammatory cytokines and chemokines in a compound-48/80-induced anaphylaxis mouse model. Wongam decreased histamine release and the expression of proinflammatory cytokines in HMC-1 and RBL-2H3 cells. Wongam treatment downregulated the expression of chemokines, T helper 2 cytokines, and cell surface antigens in PMA/A23187-stimulated HMC-1 cells. We confirmed that these effects were associated with the inhibition of the MAPK and NF-κB signaling pathways by Wongam. The present study suggests that Wongam ameliorates mast-cell-mediated allergic inflammatory responses by reducing mast cell activation and may serve as an effective agent for the prevention and treatment of allergic inflammatory responses.